Establishing a library as an Open Science partner for economic research through impact-oriented public relations work - Siegfried, Doreen (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2024)
The article describes how ZBW – Leibniz Information Centre for Economics is working to strengthen its perception as a competent partner and promoter of Open Science for its target group of economic researchers. This article describes the challenges, goals and opportunities of impact-oriented communication for libraries using the example of the ZBW. The article describes the path from the challenges and goals of the concrete communication activities and the evaluation of the impact-oriented communication work.